Validation and quantification of extractable age pigments for determining the age of Antarctic krill (Euphausia superba) - McGaffin, AF; Nicol, S; Virtue, P; Hirano, Y; Matsuda, T; Uchida, I; Candy, SG; Kawaguchi, S (Marine Biology, 2011)
Antarctic krill, Euphausia superba, hatchedfrom eggs and maintained for four years, were sampledperiodically for age-pigment analysis. Extractable pigmentsfrom the eye and eyestalk ganglia were quantifiedusing fluorescence intensity and standardised against protein.Three peak fluorescence intensities were detected atwavelengths of excitation 280 nm, emission 625 nm (pigment1); excitation 355 nm, emission 510 nm (pigment 2);and excitation 463 nm, emission 620 nm (pigment 3).There was a positive correlation between the quantity ofpigments 1 and 3 and the age of Antarctic krill. A modelwas developed to predict age from pigment 3 and tocompare it with other age proxies (carapace length andeyeball diameter). The quantity of pigment 3 was the bestpredictor of age. The pigment method can discriminatebetween similar sized krill aged 12 and 36 months. Agepigments provide an improved tool for age estimation inAntarctic krill, particularly if used in conjunction withother demographic information.